Digitalization as a Concept for Prevention of Criminal Acts of Corruption in Indonesia Against Vulnerability in Innovation Implementation at the Regional Level - Ismail, Audaraziq; Mutiara Nelson, Febby; Wibowo, Basuki Rekso; Riyanta, Stanislaus (Dinasti Research, 2025)
This investigation aims to explore digitalization as a tool to prevent corruption at the local government level in Indonesia. A normative legal approach was used in this investigation, which analyzed secondary data, such as laws, regulations, and academic studies. This study indicated that digitalization had the potential to reduce the vulnerability to corruption by increasing transparency, accountability, and integrity in local government governance. By integrating e-catalogs and local government information systems, the government can create a tighter oversight mechanism for procuring goods and services. Several limitations in implementation are still to be found, including differences in infrastructure and technological readiness in various regions, which hinder the effectiveness of implementing digital policies in preventing corruption. This study concludes that a comprehensive and consistent digitalization strategy across all regions is essential to strengthening law enforcement and reducing corruption in Indonesia.